Marine Pots and Traps of the South-West Coast of India: A Review of their Design, Operation and Fisheries - K. K., Prajith; S., Chinnadurai; M. P., Remesan (Fishery Technology, 2023)
Pots and traps are passive fishing gears that have a low impact on the environment and are highly selective and thus have advantages over other fishing methods. In India, pot and trap fishing are an age-old practice that is very common in inland waters. However marine trap fishing in the country is restricted to the Gulf of Mannar, Palk Bay of the South-east coast of India and the Enayam -Kadiyapattinam coastal belt of the South-west coast. Rectangular and semi-cylindrical-shaped traps are the common designs used for catching lobster and arrow-shaped traps fabricated with natural material are the common fish traps operated in India. Presently there is no recommended minimum mesh size for trap fishing in the country. A recent trend of shifting from natural material to synthetic material for fabrication of traps was observed. In India catch data from the trap fishing sector is limited. The paper discusses key issues in trap fishing and suggests recommendations for sustainable marine trap fishing in India.